China's Digital Economy : Opportunities and Risks - Zhang, Longmei (IMF Working Papers; Working Paper, 2019)
China's digital economy has expanded rapidly in recent years. While average digitalization of the economy remains lower than in advanced economies, digitalization is already high in certain regions and sectors, in particular e-commerce and fintech, and costal regions. Such transformation has boosted productivity growth, with varying impact on employment across sectors. Going forward, digitalization will continue to reshape the Chinese economy by improving efficiency, softening though not reversing, the downward trend of potential growth as the economy matures. The government should play a vital role in maximizing the benefits of digitalization while minimizing related risks, such as potential labor disruption, privacy infringement, emerging oligopolies, and financial risks.